Secularisation and Church-State Relations: Towards a Typology - Adam Liwak (Warszawskie Studia Teologiczne)
The article titled Secularization and Church-State Relations: Towards a Typology is an attempt to address the lack of clear definition of the term “secu-larisation”. The paper is divided into four parts. In the beginning, the author, tak-ing into account previous research, compiles various concepts of origin and the meaning of the term „secularisation”, including authors such as Berger, Casanova, Taylor and Mazurkiewicz.The second part presents different attitudes towards secularisation and secularism. It also explains differences between the two concepts.Moving on to the third section of the paper, the author here includes se-lected historical aspects of secularisation and the influence of this process on the state-church relationship. A historical analysis is followed by a new typology of secularisation, consisting of five different categories which are possible to apply in Political Science.In the last part of the article a preliminary attempt to analyze the term „semi-secularization” is carried out. In his research, the author outlines the ele-ments that make up that process.The absence of a single, commonly accepted definition of ‘secularisation’ suggests that the term attempts to embody not one, but a variety of distinctive patterns of the phenomenon; thus, the analytical and descriptive power of the term is weakened or lost altogether. By si$ing through and classifying the range of definitions and theories of secularisation, while also examining aspects of the his-torical phenomenon development within the Latin West, it is possible to propose a typology comprising five different patterns of this phenomenon.